Draft Requirement of a Shovel Type Furrow Opener under Coarse Textured Soil Condition - Darmora, D P (Journal of Agricultural Engineering, 2007)
A 55 mm shovel type furrow opener of combined seed drill was selected for optimization of its design parameters. Four boot wedge angles (20, 40, 60 and 80 degree) and four rake angles (30, 40, 50 and 60 degree) of the furrow opener were investigated at four operating depths (40, 60, 80 and 100 mm). The tests were conducted in a factorial randomized block design with two replications under sandy loam and loamy sand soil conditions in an indoor soil bin for optimizing the design parameters of the furrow opener in order to minimize its draft requirement. Boot wedge as well as rake angle of 40degree was found as the optimum value under both the soil conditions. Multiple regression equations were also developed to predict the draft requirements precisely under sandy loam and loamy sand soil conditions.